2023
DOI: 10.3847/1538-4357/acd339
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray and Ultraviolet Emission of the Young Planet-hosting Star V1298 Tau from Coordinated Observations with XMM-Newton and Hubble Space Telescope

Abstract: Atmospheric mass loss plays a major role in the evolution of exoplanets. This process is driven by the stellar high-energy irradiation, especially in the first hundreds of millions of years after dissipation of the proto-planetary disk. A major source of uncertainty in modeling atmospheric photoevaporation and photochemistry is due to the lack of direct measurements of the stellar flux at extreme-UV (EUV) wavelengths. Several empirical relationships have been proposed in the past to link EUV fluxes to emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Alternatively, photolytic destruction of methane could also potentially produce a methane poor atmosphere [55], which may be feasible given the youth and high activity levels of V1298 Tau. We test this hypothesis by running self-consistent forward model using published UV spectrum of V1298 Tau [56]. However, for V1298 Tau b photochemistry does not impact the methane abundance for pressures higher than 10 −4 bar even for extreme case (1000×solar XUV flux, Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, photolytic destruction of methane could also potentially produce a methane poor atmosphere [55], which may be feasible given the youth and high activity levels of V1298 Tau. We test this hypothesis by running self-consistent forward model using published UV spectrum of V1298 Tau [56]. However, for V1298 Tau b photochemistry does not impact the methane abundance for pressures higher than 10 −4 bar even for extreme case (1000×solar XUV flux, Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Marino et al (2006) reported no substantial evidence of long-term X-ray variability in the stellar members of the approximately 100-million-yearold open cluster NGC 2516. Similarly, Maggio et al (2023) reported only a small long-term X-ray variability with an amplitude of approximately ∼2 for the 12-million-year-old young star V1298 Tau.…”
Section: Characteristic X-ray Emissionmentioning
confidence: 92%
“…The integrated XUV (X-ray + EUV, <912 Å) flux from V1298 Tau using our combination of the XSPEC model and the DEM-generated EUV spectra is 3.2 ± 0.3 × 10 −12 erg s −1 cm −2 with additional uncertainty scaling factors of 15% and 20% introduced to the SED for the FUV flux calibration and n(H I) column density uncertainties, respectively. Poppenhaeger et al (2021) and more recently Maggio et al (2023) have also estimated the total EUV flux of V1298 Tau using different sets of observations and methods than this work. Between all three sets of observations, it is clear in the data that V1298 Tau exhibits significant long-term X-ray variability, but assessing the EUV variability is more difficult given the modeldependence of the EUV estimation.…”
Section: Euv Spectrummentioning
confidence: 99%
“…dependence of the EUV estimation. The X-ray fluxes reported by Poppenhaeger et al (2021), Maggio et al (2023), and this work are listed in Table 5. Maggio et al (2023) fits emission measure distributions to two sets of observations with different X-ray fluxes labeled "quiescent" and "elevated," finding that the bulk of the difference in X-ray flux can be attributed to the enhancement of a hotter 10 7 K plasma component in the elevated state.…”
Section: Euv Spectrummentioning
confidence: 99%
See 1 more Smart Citation